Proteomic Serum Profile of Fatigued Men Receiving Localized External Beam Radiation Therapy for Non-Metastatic Prostate Cancer - Lukkahatai, Nada; Patel, Sajni; Gucek, Marjan; Hsiao, Chao-Pin; Saligan, Leorey N. (Journal of pain and symptom management, 2014)
Fatigue is the most distressing side effect of radiation therapy, and its progression etiology is unknown. This study describes proteome changes from sera of fatigued men with non-metastatic prostate cancer receiving external beam radiation therapy (EBRT). Fatigue scores, measured by the Functional Assessment of Chronic Illness Therapy-Fatigue, and serum were collected from 12 subjects at baseline (before EBRT) and at midpoint (Day 21) of EBRT. Depleted sera from both time points were analyzed using two-dimensional difference gel electrophoresis, and up/down regulated proteins were identified using liquid chromatography-tandem mass spectrometry. Western blot analyses confirmed the protein changes observed. Results showed that apolipoprotein (Apo)A1, ApoE, and transthyretin (TTR) consistently changed from baseline (Day 0) to midpoint (Day 21). The mean ApoE level of subjects with high change in fatigue (HF: n = 9) increased significantly from baseline to midpoint and were higher than in subjects with no change in fatigue. The mean ApoA1 level was higher in HF subjects at baseline and at midpoint than in no fatigue subjects at both time points. The mean TTR level of no fatigue subjects was higher at baseline and midpoint than in HF subjects. These ApoE, ApoA1, and TTR results may assist in understanding pathways that can explain fatigue progression etiology in this clinical population.